2015
DOI: 10.4103/1119-3077.151788
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude of dentists toward implant retained restorations in Saudi Arabia

Abstract: Knowledge of SP and GDP for selection of implant-retained restorations was broadly in line with standard evidence. The clinical use of CRR was greater in comparison to SRR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…The overall response rate was 81% that is comparatively high in comparison to questionnaire-based studies previously. 15,16 This could be attributed to the immediate concern of the participants (health care professionals) to contribute towards finding solutions to curb the contagious viral pandemic. HCPs routinely take standard precautions considering each patient as infected i.e able to transmit infection.…”
Section: Discussionmentioning
confidence: 99%
“…The overall response rate was 81% that is comparatively high in comparison to questionnaire-based studies previously. 15,16 This could be attributed to the immediate concern of the participants (health care professionals) to contribute towards finding solutions to curb the contagious viral pandemic. HCPs routinely take standard precautions considering each patient as infected i.e able to transmit infection.…”
Section: Discussionmentioning
confidence: 99%
“…The excellent marginal integrity and retrievability are the main advantages of screw-retained restorations but have disadvantages such as open screw access holes and need for optimal implant positioning which have been proposed to stabilize veneering material and compromise occlusion. The total cost of implant treatment increases due to the sophisticated clinical and laboratory procedures of screw-retained restorations (Vohra and Habib, 2014, Millen et al, 2015, Wittneben et al, 2014). Although there is no absolute way of restoring the implant, screw retention still has many attributes and, when possible, should be considered the optimal solution (Assaf and Gharbyeh, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…8 Implant placement location, poor oral hygiene, the patient's medical condition, and patient noncompliance are also reasons that may underlie implant therapy complications. 7,8,13 A recent study in the Eastern Province of Saudi Arabia indicated that far more non-Saudis than Saudis practiced implant dentistry. 8 This was attributed to the recruitment of a large number of non-Saudi dentists into the private sector due to an increased demand for implant therapy.…”
Section: Introductionmentioning
confidence: 99%